Risk Factors of Malignant Glaucoma Occurrence after Glaucoma Surgery - Karolina Krix-Jachym; Tomasz Żarnowski; Marek Rękas (Journal of Ophthalmology)
Purpose. The aim of this study was twofold: first, to evaluate the predisposing factors for occurrence of malignant glaucoma and second, to compare frequency of malignant glaucoma depending on the type of primary glaucoma surgery. Methods. Retrospective analysis was performed in 1689 consecutive patients who underwent glaucoma surgery alone or combined with phacoemulsification. Data collected included the type of surgery, width of the filtration angle, presence or absence of malignant glaucoma in the postoperative period, and time from the primary surgery to malignant glaucoma occurrence. Results. Malignant glaucoma occurred in 22 eyes that amounted to 1.3% of cases among all surgery performed. Mean time from glaucoma surgery to malignant glaucoma occurrence was 61.4 ± 190.5 days. Among patients with penetrating surgery, malignant glaucoma occurred in 2.3% of patients, whereas after nonpenetrating operations, such complication was not found (p=0.00004). Malignant glaucoma occurred more often in patients with shallow iridocorneal angle (p=0.0013). Conclusions. The risk of malignant glaucoma development is associated with penetrating characteristic of glaucoma surgery, after which this complication appears and its occurrence is higher in eyes with shallow iridocorneal angle. The risk of malignant glaucoma after trabeculectomy compared to iridencleisis as well as after phacotrabeculectomy compared to phacoiridencleisis is equivalent.